Are Medical Students Aware About Their Own Oral Health? A Cross Sectional Study in South Gujarat, India - NB Patel; Yash D Patel; Nixat J Patel (Medsci Publications, 2020)
Introduction: The awareness of health providers and their attitudes towards their oral health could reflect their approach toward oral health in future medical practice. Objectives: The present study was conducted to assess the oral hygiene awareness of the undergraduate students a medical college in Southern part of Gujarat state in India. Material and Method: A descriptive cross-sectional study was been conducted. A self-structured, pre- tested questionnaire was used in the study for assessing the oral hygiene knowledge and awareness. The questionnaire consisted details regarding the various socio demographic details, questions regarding brushing, importance of oral health etc. A 15-point score developed to score the awareness about the oral health. Results: The results revealed that the all the undergraduate students had 100% knowledge regarding the number of teeth present in the permanent dentition. Mean knowledge score was 7.5 out of 15. Boys has lower score compared to girls but the difference was non-significant (p>0.05) Conclusion: We concluded that the awareness of the undergraduate students was not satisfactory. Hence, a comprehensive program regarding oral hygiene must be implemented, starting from their first year of education.